Acute kidney injury in malaria patients at a hemodialysis center in Angola: Lesión renal aguda en pacientes con malaria en un Centro de Hemodiálisis de Angola - Paulo Chipepe, Laurinda Nené Catanga (2024)
Introduction: Malaria is a serious disease that has among its complication’s acute kidney injury, as a consequence of a sudden decline in glomerular filtration, leading the patient to hemodialysis treatment. Objective: Estimate the prevalence of acute kidney injury in patients with malaria treated at the hemodialysis center of the municipality of Lobito, in the period 2018 to 2022. Materials and methods: Observational, descriptive, cross-sectional, retrospective study. Study population: total cases treated at the hemodialysis center in the study period (n=861). Inclusion criteria: malaria patients complicated with acute kidney injury. Sample consisting of 387 patients. The data were collected from the hospital's digital renal case management platform, and treated with descriptive statistics through absolute frequency and percentage. Results: In the period there was an increase in prevalence, with a minimum in 2018 with 18.6 % and a maximum in 2022 with 86.7 % of cases (130/150). There was a predominance of the male sex (55.8%), the most vulnerable age group were young people 20 years old or younger, followed by the group from 21 to 35 years old, the upper area of Lobito, in relation to origin, remained in the period predominated with 51.4 % of cases, followed by the low zone with 27.9 %. The predominance of the clinical evolution of the patients was in the recovery of kidney function (125/32.3%), reaching 45 % and 43 % of the cases in the years 2020 and 2021. The month with the highest admission of cases in the center it was June (12 %) followed by December (10.3 %), with a total of 87 patients (22.5 %) being treated between the two months. The month with the lowest number of cases was February with 5.2 %. Conclusions: The prevalence of acute kidney injury in patients with malaria had a gradual increase in the study period, with a high mortality rate, which is why actions more focused on an accurate diagnosis of severe malaria are required.